EVOLUTION OF IRON SULFIDES IN COAL MEASURES OF THE DONBAS - Kurilo M.V. (My University, 1988)
Pyrite is the most common ore mineral in both coal measures and coal of the Donbas, whatever the stage of their metamorphism. Our laboratory work included X-ray, isotopic-geochemical and thermoelectric analysis and electron microscopy, as well as determination of the chemical composition and trace elements. That was how we studied more than 100 samples with sulfide mineralization. Our work has shown that during postdiagenetic alteration of the Donbas coal measures, iron sulfides were transformed in the order melnikovite → marcasite → pyrite → → pyrrhotite. Pyrite occurs at all stages of lithogenesis and is so-called 'continuous' mineral, whose composition and properties changed with each successive stage of that process. Other iron sulfides are characteristic only of individual stages and can serve as mineral indicators of a certain range of thermodynamic conditions.